Destitution Economies: Circuits of Value in Asylum, Refugee, and Migration Control - Coddington, Kate; Conlon, Deirdre; Martin, Lauren L. (Annals of the American Association of Geographers, 2020)
In this article, we argue that destitution economies of migration control are specific circuits of exchange and value constituted by migration control practices that produce migrant and refugee destitution. Comparative analysis of three case studies, including border encampment in Thailand, deprivation in U.S. immigration detention centers, and deterrence through destitution in the United Kingdom, demonstrate that circuits of value depend on the detachment of workers from citizenship and simultaneously produce both migrant destitution and new forms of value production. Within destitution economies, migration and asylum's particular juridico-political position as domestic, foreign, and securitized allows legal regimes to produce migrants and asylum seekers as distinct economic subjects: forsaken recipients of aid. Although they might also work for pay, we argue that destitute migrants and asylum seekers have value for others through the grinding labor of living in poverty. That is, in their categorization as migrants and asylum seekers, they occupy a particular position in relation to economic circuits. These economic circuits of migration control, in turn, rely on the destitution of mobile people. Our approach advances political geographies of migration, bordering, and exclusion as well as economic geographies of marketization and value, arguing that the predominance of political analysis and critique of immigration and asylum regimes obscures how those regimes produce circuits of value in and through law, state practices, and exclusion. Furthermore, law, state power, and forced mobility constitute circuits of value and marketization. Conceptualizing these migration control practices as destitution economies illuminates novel transformations of the political and economic geographies of migration, borders, and inequality.